Effectiveness and Challenges of Tele Optometry in Pakistan - Faiza Ilyas; Maher Mustansar Ali Qasim; Rimsha Ali; Maira Sharafat; Salyha Ilyas; Hafiz Zohaib Hassan; Babar Ali (Journal of Health, Wellness and Community Research, 2025)
Background: Tele-optometry, the remote delivery of optometric care through digital platforms, has gained significant attention as a means to improve access, continuity, and efficiency of eye care, particularly in low- and middle-income countries where infrastructural and geographic barriers limit service availability. However, evidence on its implementation, effectiveness, and adoption challenges in Pakistan remains scarce. Objective: This study aimed to assess the effectiveness and barriers associated with tele-optometry practice among registered optometrists in Pakistan, focusing on their awareness, familiarity, willingness to adopt, and perceived challenges in integrating tele-optometry into routine care. Methods: A cross-sectional survey was conducted between January and April 2024 among 15 optometrists recruited via convenience sampling. Data were collected using a self-administered online questionnaire capturing demographics, platform awareness, training, perceived effectiveness factors, and operational challenges. Descriptive statistics and exact tests were performed using SPSS 25. Results: Awareness of tele-optometry platforms was moderate (66.7%), but willingness to adopt was high (93.3%, p=0.001). Key enablers included awareness and promotion (46.7%) and infrastructure (33.3%), while major barriers were limited public awareness (33.3%) and reimbursement issues (20–26.7%). Conclusion: Despite limited knowledge and training, Pakistani optometrists demonstrate strong readiness to adopt tele-optometry, underscoring the need for targeted training, clearer reimbursement structures, and patient education to facilitate integration into eye-care delivery. Keywords: Tele-optometry, telehealth, eye care, optometry practice, healthcare delivery, Pakistan.